figoveck38

2022-11-21

Solve ${y}^{\prime }\left(t\right)=\mathrm{sin}\left(t\right)+{\int }_{0}^{t}y\left(x\right)\mathrm{cos}\left(t-x\right)dx$ by Laplace transform
My try:
I applied Laplace transform on both sides of the equation.
$sL\left\{y\left(t\right)\right\}=\frac{1}{{s}^{2}+1}+L\left\{cos\left(t\right)\ast y\left(t\right)\right\}\phantom{\rule{thickmathspace}{0ex}}⟹\phantom{\rule{thickmathspace}{0ex}}sL\left\{y\left(t\right)\right\}=\frac{1}{{s}^{2}+1}+L\left\{cos\left(t\right)\right\}×L\left\{y\left(t\right)\right\}$
Now, I'm stuck on applying the inverse Laplace transform on (*) to find $y\left(t\right)$

Zackary Hatfield

$sL\left\{y\left(t\right)\right\}\left(s\right)=\frac{1}{{s}^{2}+1}+L\left\{cos\left(t\right)\right\}\left(s\right)×L\left\{y\left(t\right)\right\}\left(s\right)$
using
$L\left\{cos\left(t\right)\right\}\left(s\right)=\frac{s}{{s}^{2}+1}$
I rather get
$L\left\{y\left(t\right)\right\}\left(s\right)=\frac{1}{{s}^{3}}$
which is now standard to solve.

evitagimm9h

$sL\left\{y\left(t\right)\right\}=\frac{1}{{s}^{2}+1}+L\left\{cos\left(t\right)\ast y\left(t\right)\right\}$
$sL\left\{y\left(t\right)\right\}=\frac{1}{{s}^{2}+1}+L\left\{y\left(t\right)\right\}\ast \frac{s}{{s}^{2}+1}$
$L\left\{y\left(t\right)\right\}\left(s-\frac{s}{{s}^{2}+1}\right)=\frac{1}{{s}^{2}+1}$
Here you made a mistake I guess
$L\left\{y\left(t\right)\right\}\left(\frac{{s}^{3}-s+s}{{s}^{2}+1}\right)=\frac{1}{{s}^{2}+1}$
$L\left\{y\left(t\right)\right\}=\frac{1}{{s}^{3}}$

Do you have a similar question?